Quality of Life of People with Mental Illness Who Lives in the Community in Sarawak - Saloma, Pawi; Zabidah, Putit; Rekaya Vincent, Balang; Jane, Buncuan (Malaysian Psychiatric Association, 2012)
This study explores the quality of life, social integration and the effects of perceived stigma of people with mental illness living in the community. Adopting a complimentary mixed method, this study was represented by 165 people with mental illness in Kuching, Sibu and Miri. Findings indicated that the quality of life scale was poor, 49.67% and 78.43% often experienced stigma. Anticipated stigma 43.79%; 16.99% all the time and 4.58% never experienced stigma. Findings also noted that people with mental illness living in the community are still largely depending on and needed continuous support from their family members/carers for financial aid and their living arrangement for a “better” quality of life. Where treatment is concerned, follow up care at home by health care providers continue to play a significant role. In order to “erase” the perceived or stigma experienced, establishing therapeutic relationship, communication and creating awareness on “stigma discrimination paradigm” poses a phenomenal challenge in the current misrepresentations of mental health messages.